Are Laws Needed for Public Management Reforms? : An International Comparison - Lienert, Ian (IMF Working Papers; Working Paper ;, 2005)
There has been widespread adoption of new laws to support new public management. In many countries that have implemented comprehensive and deep reforms, new or amended laws have fundamentally changed the role of the state and the budget processes supporting it. Paradoxically, far-reaching modifications to the legal framework for public management have been strongest in countries that often rely on executive decrees for introducing reforms. This reflects the fundamental nature of the changes, including introducing performanceoriented budgeting and enhancing fiscal transparency and accountability. Differences in political systems, policy preoccupations, administrative arrangements and legal cultures will prevent globalization of the legal framework for public management.